Elusive π-helical peptide foldamers spotted by chiroptical studies. Issue 5 (17th December 2019) - Di Silvio, Sergio; Bologna, Fabio; Milli, Lorenzo; Giuri, Demetra; Zanna, Nicola; Castellucci, Nicola; Monari, Magda; Calvaresi, Matteo; Górecki, Marcin; Angelici, Gaetano; Tomasini, Claudia; Pescitelli, Gennaro
Abstract : A series of oligomers containing alternate l -Ala and pGlu (pyroglutamic acid) both in the L and D form have been prepared and conformationally investigated by X-ray, NMR, UV/ECD, IR/VCD and molecular modelling. Abstract : A series of oligomers containing alternate l -Ala and pGlu (pyroglutamic acid) both in the L and D form have been prepared and conformationally investigated by X-ray, NMR, UV/ECD, IR/VCD and molecular modelling. X-ray diffraction analysis was possible for the shortest oligomers LL-1 and LD-1 . Molecular dynamics simulations of the oligomers demonstrated that the energy landscapes of the LL -series are broad. In contrast, the energy landscapes of the LD -series are characterized by well-defined minima corresponding to specific conformational structures. A single well-defined minimum exists in the energy landscape of the largest oligomer LD-8, corresponding to a precise conformation, characterized by i + 5 → i N–H⋯OC hydrogen bonds, typical of a π-helix. ECD and VCD spectra were measured to identify the chiroptical profiles of the oligomers. The most striking element in the ECD spectra of the LD -series is their exceptionally strong intensity, which confirms that these polypeptides attain a high degree of helical order. VCD spectra for the LD -series are well reproduced by frequency calculations when π-helix folds are employed as input structures, suggesting that a symmetrical VCD couplet around 1720 cm −1 can be taken as the VCD signature of π-helices.